Islamic Marketing within the Digital Economy: Ethical and Sustainable Practices in Indonesia’s Cellular Services Sector - Muhammad Umar MayaPutra; Yusrizal (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
Islamic marketing represents an ethical–spiritual paradigm that situates marketing activities within a framework of moral accountability grounded in the principles of tawhid, al-‘adl (justice), sidq (honesty), amanah (trustworthiness), and ihsan (benevolence). Unlike conventional marketing approaches that prioritize profit maximization, Islamic marketing emphasizes a balanced integration of economic objectives, spiritual values, and social welfare. This study aims to analyze the application of Islamic marketing principles within Indonesia’s rapidly expanding cellular industry, characterized by increasing internet penetration and digital transformation. Implementing content analysis with systematic literature review methodology, this study synthesizes scholarly works on Islamic marketing, fiqh muamalah, digital marketing, and telecommunications. The findings indicate that Islamic marketing principles can enhance consumer trust, promote pricing transparency, ensure halal and secure digital services, and strengthen corporate responsibility in consumer data protection. Nevertheless, a persistent gap remains between Sharia based normative ideals and operational practices, as evidenced by unequal service accessibility, opaque pricing structures, and the limited internalization of ethical values in marketing strategies. This study concludes that the consistent integration of Islamic marketing values not only reinforces ethical compliance but also functions as a strategic resource for achieving sustainable competitive advantage, contributing to the development of a just, inclusive, and morally accountable digital marketplace. Islamic marketing merepresentasikan suatu paradigma etika–spiritual yang menempatkan aktivitas pemasaran dalam kerangka tanggung jawab moral dan sosial yang berlandaskan prinsip tawhid, al-‘adl (keadilan), sidq (kejujuran), amanah (kepercayaan), dan ihsan (kebajikan). Berbeda dengan pendekatan pemasaran konvensional yang berorientasi pada maksimalisasi laba, Islamic marketing menekankan keseimbangan antara tujuan ekonomi, nilai spiritual, dan kesejahteraan sosial. Penelitian ini bertujuan untuk menganalisis penerapan prinsip prinsip Islamic marketing dalam konteks industri seluler Indonesia yang mengalami pertumbuhan pesat seiring meningkatnya penetrasi internet dan digitalisasi layanan. Metode yang digunakan adalah content analysis dengan systematic literature review terhadap studi-studi akademik terkait Islamic marketing, fiqh muamalah, pemasaran digital, dan industri telekomunikasi. Hasil kajian menunjukkan bahwa prinsip Islamic marketing berpotensi memperkuat kepercayaan konsumen, mendorong transparansi harga, memastikan layanan digital yang halal dan aman, serta meningkatkan tanggung jawab perusahaan dalam perlindungan data konsumen. Namun demikian, masih terdapat kesenjangan antara ideal normatif syariah dan praktik operasional, yang tercermin dalam ketimpangan akses layanan, kurangnya transparansi biaya, dan lemahnya internalisasi nilai etika dalam strategi pemasaran. Studi ini menegaskan bahwa integrasi nilai-nilai Islamic marketing secara konsisten dapat menjadi sumber keunggulan kompetitif berkelanjutan sekaligus instrumen moral untuk membangun ekosistem digital yang adil, inklusif, dan berorientasi pada kemaslahatan masyarakat.